Demographic Disparities Using Ranked-Choice Voting? Ranking Difficulty, Under-Voting, and the 2020 Democratic Primary - Coll, Joseph A. (2021)
Ranked choice voting (RCV) has become increasingly popular in recent years, as more jurisdictions in the US adopt the voting system for local, state, and federal elections. Though previous studies have found potential benefits of RCV, some evidence suggests ranking multiple candidates instead of choosing one most preferred candidate may be difficult, with potential demographic disparities linked to age, gender, or racial or ethnic identity. Further, these difficulties have been assumed to cause individuals to improperly fill out RCV ballots, such as ranking too many or not enough candidates. This study seeks to answer three interrelated questions: 1) Which demographic groups find it difficult to rank candidates in RCV elections? 2) Who is more likely to cast under-voted ballots (not ranking all candidates)? 3) Is there a relationship between finding RCV voting difficult and the likelihood of casting an under-voted ballot? Using unique national survey data of 2020 Democratic primary candidate preferences, the results indicate most respondents find ranking candidates easy, but older, less interested, and more ideologically conservative individuals find it more difficult. In a hypothetical ranking of primary candidates, 12% of respondents under-voted (did not rank all options). Despite their perceived increased difficulty, older individuals were less likely to under-vote their ballot. No other demographic groups consistently experienced systematic differences in ranking difficulty or under-voting across a series of model specifications. These findings support previous evidence of older voters having increased difficulty, but challenge research assuming difficulty leads to under-voting, and that racial and ethnic groups are disadvantaged by RCV.